2016
DOI: 10.1136/bmjopen-2015-008698
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sources and sodium intake in a sample of Australian preschool children

Abstract: ObjectivesTo assess dietary sodium intake and the food sources of sodium in a sample of Australian preschool children.DesignCross-sectional.SettingMothers were followed up when children were approximately 3.5 years of age after participating in a cluster randomised controlled trial: the Melbourne Infant Feeding Activity and Nutrition Trial Program.Participants251 Australian children aged 3.5±0.19 (SD) years.Primary and secondary outcome measuresThe average daily sodium intake was determined using three unsched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
(37 reference statements)
2
28
1
Order By: Relevance
“…The present study provides an important processed food classification system in Australia that will enable researchers to readily evaluate the dietary intake of population groups with respect to food processing. For example, in a previous study, we applied the NOVA system to determine the contribution of the level of processing to daily sodium intake in a sample of Australian pre-school children and found that ULP foods accounted for 48% of total daily sodium intake compared to either P foods (35%) or MP foods (16%) (31) . These data provided important information on processed food dietary patterns, particularly the contribution of high sodium ULP foods in young Australian children's diets.…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides an important processed food classification system in Australia that will enable researchers to readily evaluate the dietary intake of population groups with respect to food processing. For example, in a previous study, we applied the NOVA system to determine the contribution of the level of processing to daily sodium intake in a sample of Australian pre-school children and found that ULP foods accounted for 48% of total daily sodium intake compared to either P foods (35%) or MP foods (16%) (31) . These data provided important information on processed food dietary patterns, particularly the contribution of high sodium ULP foods in young Australian children's diets.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising since in most high-income countries, bread is the major source of sodium in the diet. 22,[50][51][52] Salt in breads, as in other processed foods, provides important functions such as texture, preservation, and taste. However, many industrial bread companies allow salt levels in their products to reach unnecessarily high levels.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from two recent cross-sectional studies have shown that ULP foods make a significant contribution to young children's total dietary Na intake. We previously assessed the contribution from the level of processing to total daily Na intake in a sample of Australian children aged 3•5 years and found that ULP foods contributed 48 % of total daily Na intake compared with P (35 %) and MP (16 %) foods (28) . Similarly, utilizing 2 d of dietary data, Sparrenberger et al found in 204 Brazilian children aged 2-10 years that ULP foods contributed 49 % of total Na, whereas MP foods contributed only 17 % and PCI 35 % (29) .…”
Section: Discussionmentioning
confidence: 99%